The Transcription Factor Hobit Identifies Human Cytotoxic CD4+ T Cells - Oja, Anna E.; Vieira Braga, Felipe A.; Remmerswaal, Ester B. M.; Kragten, Natasja A. M.; Hertoghs, Kirsten M. L.; Zuo, Jianmin; Moss, Paul A.; van Lier, René A. W.; van Gisbergen, Klaas P. J. M.; Hombrink, Pleun (Frontiers in Immunology, 2017)
The T cell lineage is commonly divided into CD4-expressing helper T cells that polarize immune responses through cytokine secretion and CD8-expressing cytotoxic T cells that eliminate infected target cells by virtue of the release of cytotoxic molecules. Recently, a population of CD4+ T cells that conforms to the phenotype of cytotoxic CD8+ T cells has received increased recognition. These cytotoxic CD4+ T cells display constitutive expression of granzyme B and perforin at the protein level and mediate HLA class II-dependent killing of target cells. In humans, this cytotoxic profile is found within the human cytomegalovirus (hCMV)-specific, but not within the influenza- or Epstein–Barr virus-specific CD4+ T cell populations, suggesting that, in particular, hCMV infection induces the formation of cytotoxic CD4+ T cells. We have previously described that the transcription factor Homolog of Blimp-1 in T cells (Hobit) is specifically upregulated in CD45RA+ effector CD8+ T cells that arise after hCMV infection. Here, we describe the expression pattern of Hobit in human CD4+ T cells. We found Hobit expression in cytotoxic CD4+ T cells and accumulation of Hobit+ CD4+ T cells after primary hCMV infection. The Hobit+ CD4+ T cells displayed highly overlapping characteristics with Hobit+ CD8+ T cells, including the expression of cytotoxic molecules, T-bet, and CX3CR1. Interestingly, γδ+ T cells that arise after hCMV infection also upregulate Hobit expression and display a similar effector phenotype as cytotoxic CD4+ and CD8+ T cells. These findings suggest a shared differentiation pathway in CD4+, CD8+, and γδ+ T cells that may involve Hobit-driven acquisition of long-lived cytotoxic effector function.